Erratum: KAZUSHIGE MINOURA & LAURENCE A. MOUND (2019) The world species of Ophthalmothrips Hood (Thysanoptera; Phlaeothripidae), with new records from Africa, China and Japan. Zootaxa, 4623 (3): 555–562. - Minoura, Kazushige; Mound, Laurence A. (Zootaxa, 2019)
N/A